MENINGKATKAN KEMAMPUAN PENJUMLAHAN 1 SAMPAI 10 MELALUI KANTONG BILANGAN BAGI ANAK TUNAGRAHITA RINGAN - Sofiani - Sofiani (Jurnal Penelitian Pendidikan Khusus, 2013)
This study begins with the discovery of mild mental retardation children class DII / C is not able to understand the sum of a lot of things. This is because teachers in delivering the material value of the place is always caramah method, questions and answers, penungasan, and just write problems on the board without the use of media or means to support the child's success in understanding the concept of addition. The studies aim of this is to improve the ability of the sum of many objects from 1 to 10 mild mental retardation in children class II / C (Mi, Ir, and Fr) in the class of DII / C in SLB Muaro Budi Selayo District. Solok through the use of bag numbers.